2023
DOI: 10.5469/neuroint.2022.00283
|View full text |Cite
|
Sign up to set email alerts
|

AXS Vecta 0.071–0.074 Inch Aspiration Catheters for Mechanical Thrombectomy: Case Series and Literature Review

Abstract: Aspiration catheters are widely used for thrombectomy either alone or in combination with a stent-retriever, with a distal inner diameter and trackability keys to their success. In an illustrative case series, we report our clinical experience with AXS Vecta (Stryker Neurovascular, Fremont, CA, USA), available in both 0.071-inch and 0.074-inch distal inner diameters, including the first 2 Vecta 74 cases reported. A literature review on AXS Vecta is also provided. In our series, 9 thrombectomies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The rates of procedural success and recanalization at the first attempt, along with the null incidence of complications related to REACT catheters, demonstrate the safety and effectiveness of the devices, in terms of clinical experience [ 25 ]. Another recent study [ 26 ] reported initial experience in 9 patients with AXS Vecta 71 and 74 for mechanical thrombectomy using aspiration and combination techniques for the purpose of assessing their safety and efficacy, resulting in successful revascularization in a similar proportion of cases as previously published studies (89%), using both ADAPT and the stent-retriever plus a local aspiration technique, without complications.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of procedural success and recanalization at the first attempt, along with the null incidence of complications related to REACT catheters, demonstrate the safety and effectiveness of the devices, in terms of clinical experience [ 25 ]. Another recent study [ 26 ] reported initial experience in 9 patients with AXS Vecta 71 and 74 for mechanical thrombectomy using aspiration and combination techniques for the purpose of assessing their safety and efficacy, resulting in successful revascularization in a similar proportion of cases as previously published studies (89%), using both ADAPT and the stent-retriever plus a local aspiration technique, without complications.…”
Section: Discussionmentioning
confidence: 99%